O método da jornalista Leda Nagle nas entrevistas do programa sem censura - Medeiros, Kiára Mary Fialho (2017)
This dissertation intends to unravel the method of interview of the journalist Leda Nagle, analyzing mainly the process documents used daily for the production of the program No Censorship, commanded by the interviewer and journalist in Rede Brasil. The purpose of the paper is to analyze traces left through manuscripts, drafts, handwritten or by digital means, as well as diaries, personal notes, newspaper clippings, photographs, excerpts from dialogues on social networks, guidelines and emails that have been made Part of the creative process of Leda Nagle in the program No Censorship, in addition to analyzes of programs already shown. Based on the assumption that the materials used to construct the journalistic product are similar in the different forms of publication, we will use as basis the theoretical foundation proposed by SALLES (1998), MEDINA (1996) and MOURA (2007), besides investigating the various types Of interviews used by our press in the day to day, as well as to investigate if, in fact, the dialogic interview is the main brand of journalist and interviewer Leda Nagle.